2010
DOI: 10.1021/bi100513u
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Analysis of an Enzyme-Catalyzed Pseudo-Deglycosylation Reaction: Mechanism of Desialylation in Sialidases

Abstract: The Micromonospora viridifaciens Y370G inverting mutant sialidase has been found to possess beta-sialidase activity with various fluoro-substituted phenyl beta-sialosides. A reagent panel of seven mono- and difluorophenyl beta-d-sialosides was synthesized, and these compounds were used, in conjunction with the parent phenyl beta-d-sialoside, to probe the mechanism of M. viridifaciens Y370G mutant sialidase-catalyzed hydrolyses. These hydrolysis reactions mimic the deglycosylation reaction step of the crucial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For example, had we detected an estimated 10% of the 2,3-isomer in the presence of the 2,6-isomer as reaction products (Figures S7 and S8a, Supporting Information) and used the Haldane equation to calculate a free energy difference between the two regioisomers of >9 kJ mol –1 . However, in a previous report, we suggested that Mv NA Y370G-mediated catalysis proceeds via a transition state that involves no general acid catalysis (Figure c), a situation that occurs because the catalytic glutamate is likely to be deprotonated in the mutant enzyme ground state . In contrast, the transition state for the Mv NA-catalyzed glycosylation has an addition proton that bridges between the nucleophilic tyrosine and the general base glutamate , (Figure a).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, had we detected an estimated 10% of the 2,3-isomer in the presence of the 2,6-isomer as reaction products (Figures S7 and S8a, Supporting Information) and used the Haldane equation to calculate a free energy difference between the two regioisomers of >9 kJ mol –1 . However, in a previous report, we suggested that Mv NA Y370G-mediated catalysis proceeds via a transition state that involves no general acid catalysis (Figure c), a situation that occurs because the catalytic glutamate is likely to be deprotonated in the mutant enzyme ground state . In contrast, the transition state for the Mv NA-catalyzed glycosylation has an addition proton that bridges between the nucleophilic tyrosine and the general base glutamate , (Figure a).…”
Section: Discussionmentioning
confidence: 72%
“…Pyridine and acetic acid were purchased from Anachemia, and sodium acetate and magnesium chloride were purchased from Caledon Laboratories Ltd. All other chemicals, reagents, and enzymes were purchased from Sigma-Aldrich. Ph-βNeu5Ac and 2FPh-βNeu5Ac were synthesized according to literature procedures. , …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aryl glycosides bearing different leaving groups are chromogenic substrates that can be used for detailed kinetic analysis of retaining glycosides [2][3][4]. The kinetic parameters of YicI were measured for the hydrolysis of the aryl ␣-xyloside substrates.…”
Section: Kinetic Analysis Of Aryl˛-xylosides As Wild-type Yici Substrmentioning
confidence: 99%
“…In addition, synthetic O-aryl glycosides with chromogenic or fluorogenic aglycons are invaluable substrates for the study of enzyme kinetics [2][3][4]. Therefore, the chemical synthesis of O-aryl glycosides is an interesting topic in carbohydrate chemistry.…”
Section: Introductionmentioning
confidence: 99%